Rice Nitrogen Use Efficiency and Traits Affected by Different Nitrogen Fertilization Management - Modir, Elham; Barari Tari, Davood; Amiri, Ebrahim; Nickneja, Yousef; Fallah, Hormoz (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
In order to evaluate nitrogen use efficiency (NUE) on rice at different nitrogenfertilization management, an experiment was carried out in field of south Caspian coastal sea, Mazandaran province, Babol, Iran (36° 29 N, 52 23 E, altitude, 23.7 m) over two cropping seasons of 2015 and 2016. An experiment was designed and laid out in factorial based on Randomized Completely Block Design with three replica- tions. The factors were amount of nitrogen (50, 90, 130, 170 Kg N ha-1) and nitrogen splitting were at four levels (T1: 70% base + 30% maximum tillering stage; T2: 33.33% base + 33.33% maximum tillering stage + 33.33% panicle initiation; T3: 25% base + 50% maximum tillering stage + 25% panicle initiation; T4: 25% base + 25% maximum tillering stage + 50% panicle initiation). Results showed that nitrogen amount had a significant effect on aerial nitrogen, grain nitrogen, biomass in harvesting day, ANUE and PNUE at 0.01 probability level also nitrogen of above ground organ, biomass in harvesting day, NHI, ANUE and PNUE influenced signifi- cantly by nitrogen splitting. Most grain nitrogen was produced in use of 170 kg N ha-1 and T4 splitting level. In the review of an interaction effect, the interaction between Year×Splitting×Amount was significant for grain nitrogen trait at the 0.01 probability level. According to results apply 170 kg N ha-1 in way of 25% base + 25% in maximum tillering stage + 50% in panicle initiation for best attributes of this variety were recommended.